K-shell Photoionization of the N+, NH+ and NH2+ ions. Issue 14 (January 2020) - Mclaughlin, B M; Mosniert, J P; Kennedy, E T; Sokell, E; Bizau, J M; Cubaynes, D; Guilbaud, S; Carniato, S
Synopsis: Single and double photoionization cross-sections in the photon region straddling the nitrogen K-edge and up to photon energies of ∼450 eV, for the atomic N + and molecular NH + and NH 2 + species were measured at the SOLEIL radiation facility in Orsay, France. The measurements are compared with theoretical estimates.